Levothyroxine and Non-alcoholic Fatty Liver Disease: A Mini Review - Singha, Partha S.; Ghosh, Suvendu; Ghosh, Debosree (Mini Reviews in Medicinal Chemistry, 2024)
Levothyroxine or l-thyroxine is artificially manufactured thyroxine, which is used as a drug to treat underactive thyroid conditions in humans. The drug, levothyroxine, is consumed daily in a prescribed dose to replace the missing thyroid hormone thyroxine in an individual with an underactive thyroid, and it helps to maintain normal physiological conditions. Though it is a life-maintaining drug, it replaces the missing thyroid hormone and performs the necessary daily metabolic functions in our body. Like all other allopathic drugs, it comes with certain side effects, which include joint pain, cramps in muscle, weight gain/loss, hair loss, etc. The thyroid hormone, thyroxine, is known to mobilize fat in our body, including the ones from the hepatic system. An underactive thyroid may cause an accumulation of fat in the liver, leading to a fatty liver, which is clinically termed Non-Alcoholic Fatty Liver Disease (NAFLD). The correlation between hypothyroidism and NAFLD is now well-studied and recognized. As levothyroxine performs the functions of the missing thyroxine, it is anticipated, based on certain preliminary studies, that the drug helps to mobilize hepatic fat and thus may have a crucial role in mitigating the condition of NAFDL.
Keywords: thyroxine